International assessments as the comparative desires and the distributions of differences: infrastructures and coloniality. Issue 3 (4th May 2022) - Popkewitz, Thomas S.
ABSTRACT: The Organization of Economic, Cooperation and Development's Programme for International Student Assessment (OECD's PISA) is explored as a site of science as an actor managing a social life. Its calculations form at the interstices of multiple historical lines as a comparative reason about nations, societies, and populations. That reason is explored as (1) the affective structuring of desires; (2) the inscription of comparative principles that differentiate and distributes differences; (3) a particular modern 'homeless' consciousness of a global knowledge entangled with (4) cybernetics theory and the school alchemy, translations of the science and mathematics into the territory of schooling; and (5) ranking, charts and graphs that produce a visual culture through numbers as objects of desire. The analysis brings into view the affective structure of an imperial presence of empirical facts that differentiates people under banners of future progress, modernization, and the good life.